PENEGAKAN HUKUM TERHADAP PELAKU PEMBUANG SAMPAH YANG TIDAK PADA TEMPATNYA DI LINGKUNGAN WISATA TAMAN PANCING DESA ADAT PEMOGAN - Malo, Agustinus Ngongo (Kerta Dyatmika, 2018)
Waste management has remained a problem for the city government up to this point, necessitating extra care in order to find solutions. A very important issue following for the growth of regional development, particularly in taman pancing regency. The following issues can be identified based on the background of the problem as state above: Haw carring attitude society towards environmental hygiene on the lingkungan wisata taman pancing desa adat Pemogan; and how law enforcement and application of sanction towards the perpetrator trash disposer not in place environment on the lingkungan wisata taman pancing desa adat Pemogan. Empirical legal research is the kind that was used, and it was descriptive in nature, primary and secondary data are the sources of the information used. Observational methods and interview methods are used by the outhors of this study to collect data. Last but not least, this study analyzed qualitative data using data processing techniques. Data collection technique which the outher uses in research studied using a number theory or concept ie law enforcement theory and legal certainly. Study used as follows : (1) through participation active in activities waste management cleaning, counseling environmental cleanliness, create a clean environment, and environmentally friendly tourist and local . (2) fines and application of sanctions social like asking asked the perpetrator clean area the perpetrator of the dirt as shapes perpetrator’s responsibility.